Relevansi Ajaran Al-Qur’an dan Hadis dalam Menjawab Tantangan Moral Generasi Milenial - Kurniawan Syah Putra (lembaga Sepercenter, 2024)
Millennials face complex moral challenges amid technological advances, globalisation, and changing social values. Moral decadence, individualism, hedonism, and spiritual disorientation are major issues that threaten the character of the younger generation. This article aims to examine the relevance of the teachings of the Qur'an and hadith as solutions to the moral crisis of the millennial generation. Using a qualitative approach based on literature review, this article concludes that Qur’anic and Sunnah values such as honesty, responsibility, empathy, and piety have high urgency to be internalised through contextual Islamic character education. Education based on revelatory values has great potential in building a generation that is moral, moderate, and competitive in the digital age.